Effect of Thyroxine Hormone (T4) Addition in Feed to the Growth Rate Trachinotus Blochii, Lacepede - Tanthowi, Muhammad Imam; Tang, Usman M; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The aim of this research was to investigate the dose of Thyroxine (T4) hormone in fish meal on the growth of Bawal bintang fish (Trachinotus blochii, Lacepede). The research method used was experimental method and Complete Random Device (CRD) with four treatments and three replications. The treatments in this study were control (without thyroxine hormone), 0,3 mg Thyroxine hormone / kg of feed, 0,6 mg Thyroxine hormone / kg of feed and 0,9 mg Thyroxine hormone / kg of feed. The best result was treatment on 0,9 mg Thyroxine hormone / kg of feed with absolute growth weights (1,42 g), absolute growth length (2,34 cm), specific growth rate (6,07 %), feed efficiency (69,34 %) and survival rate (99,83 %).Keywords : Survival rate, Feed efficiency, Bawal bintang